Aspek Biologi Dan Hubungan Panjang Berat Udang Swallow (Metapenaeus Ensis), Udang Putih (Panaeus merguiensis) Dan Udang Dogol (Metapenaeus monoceros Fab.) Di Perairan Aceh Utara - ardiansyah Ardiansyah; Muhammadar Muhammadar; Dedi Fazriansyah Putra (Jurnal Kelautan dan Perikanan Indonesia, 2022)
Matang Puntong Seunuddon Village, North Aceh Regency, is a coastal area with great potential in the marine and fisheries sector. One of the potential fisheries in this region is shrimp with high economic value. This study aims to determine several aspects of biology such as identifying species including the relationship between length and weight and sex ratio. The research method used is a simple random sampling method, namely by taking a random sample of shrimp from one basket of fishermen's catch in 1 time sailing. Samples of shrimp were taken 10% of the total catch of fishermen and then measured the length and weighed. Sampling was carried out in April 2021 on the coast of Matang Puntong Village, Seunuddon, North Aceh Regency. The results showed that there were three types of shrimp, namely swallow shrimp with a length range of  95-150 cm, white shrimp with a length range of 12-90 cm, and dogol shrimp with a length range of 59-96 cm with the growth characteristics of both male and female shrimp being negative allometric. Based on the calculation of sex ratio, the ratio of male and female swallow prawns is 1:0.60 with a chi-square test value of 4.354.61,  white shrimp is 1:1 with a chi-square test of 4.353.77 and dogol shrimp with a ratio of 1:23 with a chi square test value of 4.350.63.